2023
DOI: 10.1128/spectrum.02652-22
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae Invasion Dynamics of the Chironomid Host Are Strongly Influenced by Aquatic Cell Density and Can Vary by Strain

Abstract: Vibrio cholerae is the causative agent of cholera, a significant diarrheal disease affecting millions of people worldwide. Increasing evidence suggests that the environmental facets of the V. cholerae life cycle involve symbiotic associations with aquatic arthropods, which may facilitate its environmental persistence and dissemination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Zhao et al ( 1 ) created freshwater microcosms to examine the impact of Vibrio cholerae cell density in the water on chironomid larvae. In their work, they stated that nothing is known about the dynamics and the interactions between V. cholerae and chironomids.…”
Section: Lettermentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al ( 1 ) created freshwater microcosms to examine the impact of Vibrio cholerae cell density in the water on chironomid larvae. In their work, they stated that nothing is known about the dynamics and the interactions between V. cholerae and chironomids.…”
Section: Lettermentioning
confidence: 99%
“…Zhao et al ( 1 ) found that V. cholerae in the concentration of 10 9 CFU/mL caused larval death. At this bacterial load, any bacterial species will cause larval death because of the high organic load and lack of oxygen.…”
Section: Lettermentioning
confidence: 99%